Evaluation of halpern’s “structural component” for improving critical thinking - Nieto, Ana Mª; Saiz, Carlos (The Spanish Journal of Psychology, 2008)
Halpern (1998) proposed a four-component model for promoting the transfer of critical thinking. One of them, the “structural component,” focuses on how to organize teaching so that critical thinking skills can be generalized. Here, we assess the efficiency of that type of organization. Thus, one group of university students received instruction following the suggestions specified in that component and their performance was compared with that of other university students who received instruction in the same skills but using a different procedure, and with that of a control group. In comparison with the control group, the performance of both instructed groups was better after training. However, no significant differences were observed between either instruction group; both forms of instruction afforded very similar results.